Suranyi-Unger's Economics in the Twentieth Century - Taylor, O. H. (Quarterly Journal of Economics, 1932)
Journal Article Surányi-Unger's Economics in the Twentieth Century Get access O. H. Taylor O. H. Taylor Harvard University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 46, Issue 2, February 1932, Pages 407–409, https://doi.org/10.2307/1883239 Published: 01 February 1932